Cytokine-mediated crosstalk between cancer stem cells and their inflammatory niche from the colorectal precancerous adenoma stage to the cancerous stage: Mechanisms and clinical implications - Cui, Guanglin; Wang, Ziqi; Liu, Hanzhe; Pang, Zhigang (Frontiers in Immunology, 2022)
The majority of colorectal cancers (CRCs) are thought to arise from precancerous adenomas. Upon exposure to diverse microenvironmental factors, precancerous stem cells (pCSCs) undergo complex genetic/molecular changes and gradually progress to form cancer stem cells (CSCs). Accumulative evidence suggests that the pCSC/CSC niche is an inflammatory dominated milieu that contains different cytokines that function as the key communicators between pCSCs/CSCs and their niche and have a decisive role in promoting CRC development, progression, and metastasis. In view of the importance and increasing data about cytokines in modulating pCSCs/CSC stemness properties and their significance in CRC, this review summarizes current new insights of cytokines, such as interleukin (IL)-4, IL-6, IL-8, IL-17A, IL-22, IL-23, IL-33 and interferon (IFN)-γ, involving in the modulation of pCSC/CSC properties and features in precancerous and cancerous lesions and discusses the possible mechanisms of adenoma progression to CRCs and their therapeutic potential.